A two-step mechanism for the inactivation of microtubule organizing center function at the centrosome - Jérémy Magescas; Jenny C Zonka; Jessica L Feldman (eLife, 2019)
The centrosome acts as a microtubule organizing center (MTOC), orchestrating microtubules into the mitotic spindle through its pericentriolar material (PCM). This activity is biphasic, cycling through assembly and disassembly during the cell cycle. Although hyperactive centrosomal MTOC activity is a hallmark of some cancers, little is known about how the centrosome is inactivated as an MTOC. Analysis of endogenous PCM proteins in C. elegans revealed that the PCM is composed of partially overlapping territories organized into an inner and outer sphere that are removed from the centrosome at different rates and using different behaviors. We found that phosphatases oppose the addition of PCM by mitotic kinases, ultimately catalyzing the dissolution of inner sphere PCM proteins at the end of mitosis. The nature of the PCM appears to change such that the remaining aging PCM outer sphere is mechanically ruptured by cortical pulling forces, ultimately inactivating MTOC function at the centrosome.